Relação estrutura/atividade entre lignanas e mecanismos envolvidos na vasodilatação em aorta de camundongo - Lorena Isabel Silva Maciel (2013)
Studies have shown that lignans have properties beneficial to the cardiovascular system, showing an anti-hypertensive, vasodilator and protective vascular action. The structure-activity relationship and the mechanism of action of the vasodilatory effect of lignans in mice aorta were investigated. Mice aortas were maintained in a organ system bath in Krebs-Riger saline. Cumulative concentration-response curves of lignans: grandisin, licarin A and yangambin were obtained. In aortas with functional endothelium, grandisin, licarin A and yangambin induce vasodilation effect, concentration-dependent (pIC50 = 4.30 ± 0.13,> 4.00 and 4.51 ± 0.05, respectively). In the absence of a functional endothelium the vasodilator effect of grandisin has not changed. However, the vasodilator effect of licarin A was significantly reduced and the concentration-effect curve of yangambin was shifted to the right. The same pattern of response was observed in vessels pre-incubated with L-NAME. Pre-incubation of aortic rings with ODQ promoted a shift to the right of yangambin and licarin A concentration-effect curves. Vessels pre-contracted with KCl did not reduce vascular relaxation induced by grandsin and yangambin. In medium without calcium, pre-incubation with grandisin and yangambin reduced the contraction induced by phenylephrine. Furthermore, in absence of extracellular calcium, pre-incubation with grandisin and yangambin significantly reduced the contraction induced by caffeine. Pre-incubation of the aortic rings with grandisin and yangambin reduced the intensity of fluorescence emitted by Fluo 4-AM front phenylephrine stimulation in the presence of extracellular calcium. In contrast, vessels pre-incubated with grandisin and yangambin had no significant effect on the fluorescence intensity emitted by Fluo 4-AM in the absence of extracellular calcium.The propenylbenzofuran group of licarin may be responsible for an endothelium- and nitric oxide-dependent mechanism, while the single furan group of grandisin could be related to a mechanism of action endothelium-independent and dependent of inhibition of calcium influx. The furofuran group of yangambin seem to allow a partial activation of endothelium-dependent vasodilatation and inhibition of calcium influx. Therefore, this work gives support for the development of new vasodilator drugs based on the structure of lignans.